2011
DOI: 10.1093/molehr/gar003
|View full text |Cite
|
Sign up to set email alerts
|

A genome-wide scan in affected sibling pairs with idiopathic recurrent miscarriage suggests genetic linkage

Abstract: Previously, siblings of patients with idiopathic recurrent miscarriage (IRM) have been shown to have a higher risk of miscarriage. This study comprises two parts: (i) an epidemiological part, in which we introduce data on the frequency of miscarriage among 268 siblings of 244 patients with IRM and (ii) a genetic part presenting data from a genome-wide linkage study of 38 affected sibling pairs with IRM. All IRM patients (probands) had experienced three or more miscarriages and affected siblings two or more mis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
2
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(45 citation statements)
references
References 33 publications
2
38
2
3
Order By: Relevance
“…This has restricted their efficient use in clinical studies. Genome-wide scan-based studies have been reported, although they have not reached the classical accepted statistical threshold for significance and have apparently failed to identify specific genes [12,13]. Such failure to identify RSA aetiological genes might be explained by the fact that reproduction's inherent complexity theoretically implies that mutations in hundreds of candidate genes may be responsible for the phenotype [10,14].…”
Section: Introductionmentioning
confidence: 99%
“…This has restricted their efficient use in clinical studies. Genome-wide scan-based studies have been reported, although they have not reached the classical accepted statistical threshold for significance and have apparently failed to identify specific genes [12,13]. Such failure to identify RSA aetiological genes might be explained by the fact that reproduction's inherent complexity theoretically implies that mutations in hundreds of candidate genes may be responsible for the phenotype [10,14].…”
Section: Introductionmentioning
confidence: 99%
“…Genomewide scans in affected sibling pairs with IRM have suggested a genetic linkage (11). The underlying genetic causes of IRM are complex, and it is currently unclear which genes are involved or how individual genetic variants contribute to IRM.…”
mentioning
confidence: 99%
“…At the genetic level, results from two GWAS had been published [27,28]. The Li study was a pilot study in 44 Han Chinese patients with idiopathic recurrent miscarriage (IRM) and 44 matched healthy controls and identified three regions (6q27, 9q33.1, and Xp22.1) that were significantly associated with IRM.…”
Section: Discussionmentioning
confidence: 99%